Criminal careers and early death: relationships in the Cambridge study in delinquent development - Skinner, Guy C.M. (The British journal of criminology, 2022)
Prior research shows that convicted and incarcerated persons tend to die early, but this research does not investigate the relationships between criminal career features and early death. The aim of this article is to utilize the Cambridge Study in Delinquent Development longitudinal sample of males to study this; 54 males who died early (up to age 65) are compared with 332 males who did not emigrate and did not die early. The results show that convicted offenders, early onset offenders, recidivists and chronic offenders tended to die early, but there were relatively weak relationships between early death and life-course-persistent offenders and career duration. It is concluded that much more research on the relationship between early death and criminal career features is needed, and further tests of criminological theories need to take account of the time at risk of offending.